2011
DOI: 10.3802/jgo.2011.22.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Combination of imatinib mesylate with lithium chloride and medroxyprogesterone acetate is highly active in Ishikawa endometrial carcinomain vitro

Abstract: ObjectiveThe aim of the study was to investigate whether lithium chloride and medroxyprogesterone acetate can potentiate the cytotoxicity of imatinib mesylate in human endometrial cancer in vitro and the effect of midkine in these therapies.MethodsImatinib mesylate (50 µM), lithium chloride (100 µM), medroxyprogesterone acetate (200 µM) and their combination were applied to monolayer and three dimensional cultures of human Ishikawa endometrial cancer for 72 hours. The cell proliferation index, apoptotic index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…Therefore, regardless of the status of c-kit expression, imatinib mesylate may be an effective targeting therapy for LGESS. Besides c-kit and PDGFR, c-Abl is also a tyrosine kinase that is targeted by imatinib mesylate 22 ; and some studies have reported the universal expression of c-Abl in patients with LGESS. 10,14 This fact further supports the possibility that imatinib mesylate may be an effective targeting therapy for LGESS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regardless of the status of c-kit expression, imatinib mesylate may be an effective targeting therapy for LGESS. Besides c-kit and PDGFR, c-Abl is also a tyrosine kinase that is targeted by imatinib mesylate 22 ; and some studies have reported the universal expression of c-Abl in patients with LGESS. 10,14 This fact further supports the possibility that imatinib mesylate may be an effective targeting therapy for LGESS.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were examined with a JEM-1011 TEM (JEOL, Inc., Peabody, MA, USA). Photographs of stem cell and non-stem cell spheroids applied with the lowest (1 µM) and highest (500 µM) concentrations of LiCl were captured at several different magnifications (24).…”
Section: Apoptotic Index Analysismentioning
confidence: 99%
“…The plates were inspected for colony (sphere) growth 1 week after initiation. The number of colonies within each well was counted under a microscope (Olympus BX-51; Olympus, Hamburg, Germany) and images of representative fields were captured (24).…”
Section: Apoptotic Index Analysismentioning
confidence: 99%
See 2 more Smart Citations